KOMUNIKASI INTERPERSONAL ORANG TUA TERHADAP PENANAMAN PERILAKU IBADAH SHALAT DAN MENGAJI PADA ANAK USIA SEKOLAH DASAR DI KAMPUNG CILANGKAP RT 01/RW 015 KECAMATAN TAPOS, DEPOK - Nandira Aulia Azahra, (2023)
This study aims to discuss the interpersonal communication of parents towards the inculcation of prayer and recitation behavior in elementary school-age children in Cilangkap Village RT 01/RW 015 Tapos District, Depok by using the Stimulus Organism Response theory.The method used is descriptive qualitative using primary data sources and secondary data. Data collection techniques in this study used in-depth interviews with 12 informants. The sampling technique was carried out by snowball sampling technique. The data analysis technique in this study is inductive analysis, which consists of three stages, namely, data reduction, data presentation, and drawing conclusions. The final results of this study indicate that interpersonal communication between parents and children in Cilangkap Village, RT 01/RW 015, Tapos Depok District, is carried out during free time, such as at night and on holiday. While the efforts made by parents in instilling the prayer behavior to children are not fully done, due to the lack of understanding of Islamic religious science that parents have. Most children prefer to study the recitation outside with a recite teacher so that the knowledge they gain is more diverse. Obstacles faced by parents in conducting interpersonal communication towards cultivating prayer and recitation in children include, children having difficulty understanding, children's emotions are not yet stable, children are still engrossed in their world, and environmental influences are not good. Efforts made by parents to overcome these obstacles are through communication made to children slowly, giving more attention and affection to children, and maintaining a close relationship with children.